Effect of partial preferential orientation and distortions in octahedral clusters on the photoluminescence properties of FeWO4 nanocrystals - Almeida, M. A. P.; Cavalcante, L. S. [UNESP]; Morilla-Santos, C.; Dalmaschio, C. J.; Rajagopal, S.; Li, M. Siu; Longo, Elson [UNESP] (Royal Soc Chemistry, 2012)
This communication is a report of our initial research to obtain iron tungstate (FeWO4) nanocrystals by the microwave-hydrothermal method at 170 degrees C for 45 min. X-ray diffraction patterns showed that the FeWO4 nanocrystals prepared with polyethylene glycol-200 have a partial preferential orientation in the (011) plane in relation to other nanocrystals prepared with sodium bis(2-ethylhexyl) sulfosuccinate and water. Rietveld refinement data indicates that all nanocrystals are monophasic with wolframite-type monoclinic structures and exhibit different distortions on octahedral [FeO6]/[WO6] clusters. High resolution transmission electron microcopy revealed an oriented attachment mechanism for the growth of aggregated FeWO4 nanocrystals. Finally, we observed that the photoluminescence properties of these nanocrystals are affected by partial preferential orientation in the (011) plane and distortions on [FeO6]/[WO6] clusters.